Determination of the optimal working fluid for geothermal-solar hybrid power plant through process simulation - Uy, Nicolle Kendra S. (Animo Repository, 2024)
This thesis investigated the performance of binary working fluids for a geothermal-solar hybrid power plant, utilizing Aspen Plus® for detailed process simulations. It aimed to identify an optimal binary mixture against isopentane as the benchmark fluid. Initial screening of 70 fluids led to 14 candidates, which underwent further evaluation based on multifaceted criteria including thermodynamic performance, economic viability, environmental impact, safety considerations, and process-related compatibility. Insights from eight professionals were gathered to determine the criterion weights using Analytical Hierarchy Process (AHP) and the top five working fluids were ranked using the Technique for Order of Preference by Similarity to the Ideal Solution (TOPSIS). The selected working fluids were used to combine and form binary mixtures. The optimal composition of these fluids was determined through evaluating thermal efficiency and cost-effectiveness trade-offs. The research identified an optimal binary mixture of n-butene/n-butane with a composition of 0.930/0.070, achieving a thermal efficiency of 12.88% and a cost of 1287 USD per metric ton. These results are superior to isopentane, with a thermal efficiency and cost of 11.80% and 1893 USD per metric ton, respectively. This study contributes to the research field by proposing an efficient binary fluid mixture for an ORC hybrid system, leveraging geothermal and solar resources for sustainable energy product.